THE EFFECTIVENESS OF REGIONAL REGULATION POLICY NO 15 OF 2011 CONCERNING THE RETRIBUTION OF NORTH TORAJA ANIMAL SLAUGHTERHOUSE ON INCREASING THE LOCALLY GENERATED REVENUE (PAD) IN NORTH TORAJA REGENCY - Dedi Dariston Bistolen (Program Pascasarjana Fakultas Hukum Universitas Sebelas Maret Surakarta, 2022)
This legal study has purpose to determine the Effectiveness of Regional Regulation Policy No. 15 of 2011 Regarding Charges or Retribution for Slaughterhouses on Increasing the Locally Generated Revenue. Regional Autonomy provides the authority to the local governments to determine policies and the progress of a region. Regional autonomy shifted the focus of attention from national to regional political issues. This policy is written in a Regional Regulation, in this case, the North Toraja Slaughterhouse Levy Policy which is then used as a guide to increase the locally generated revenue of the area where the policy grows and become a moral guideline to act as an effective legal function in the life of the people of North Toraja to provide retribution in order that the locally generated revenue (PAD) in the area is able to increase as well as the welfare of the people of North